Cognition, Agency and Rationality
XI, 202 p.
Keywords: As usual, the Proceedings of the International Colloquium on Cognitive Science include leading-edge work by outstanding researchers in the field. This volume contains three kinds of papers corresponding to three of the main disciplines in cognitive science: philosophy, psychology, and artificial intelligence. The title - Cognition, Agency and Rationality - captures the main issues addressed by the papers. Of course, all are concerned with cognition, but some are especially centred on the very concept of rationality, while others focus on (multiple) agency. The diversity of their disciplinary origins and standpoints not only reflects the main topics and the range of different positions presented at ICCS-97, as well as demonstrating the richness, fruitfulness and diversity of research in cognitive science today.